The Influence of Competency and Skills on ATC Personnel Performance at Jakarta Air Traffic Service Centre - Yuliati Widyasari Dwi Putri; Elfi Amir; Dwi Lestary (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Flight safety and operational efficiency are highly dependent on the performance of Air Traffic Controllers (ATC), particularly at the Jakarta Air Traffic Service Center (JATSC) under the Area Control Center (ACC) unit, which manages one of the busiest airspaces in Indonesia. This study aims to analyze the influence of competency and skills on the work performance of ATC personnel at JATSC. Competency encompasses technical, cognitive, behavioral, and emotional dimensions, while skills include operational techniques, decision-making, communication, and stress management abilities. The research employed a quantitative explanatory design, utilizing structured questionnaires distributed to 81 active ATCs, complemented by direct observation. Data were analyzed using Pearson correlation and multiple linear regression to examine the relationships and effects between variables. The results indicate that both competency and skills significantly affect ATC performance. Competent ATCs demonstrate higher situational awareness, faster decision-making, and improved coordination, while well-developed skills enhance response speed and operational precision. Moreover, the findings highlight that competency has a slightly stronger impact than skills, underscoring the importance of continuous professional development and competency-based training programs. Therefore, strengthening both competency and skills through systematic training and evaluation is crucial to improving ATC performance and maintaining flight safety within Indonesia’s increasingly complex air traffic environment.